Penyajian Teh oleh Teishu dalam Ritual Sadoo: Potret Representasi Karakter Bangsa Jepang - Reny Wiyatasari (Endogami: Jurnal Ilmiah Kajian Antropologi, 2018)
SADOO -- is one of the culture of the Japanese that still awake its sustainability in the midst of globalization and modernization. Sadoo in Japan is influenced by Zen Buddhism. Therefore sadoo is believed to be one of the richest cultures of meaning and value of life, such as social values, discipline, beauty, and etiquette. It is illustrated by the strict rules of conduct carried out and observed by the teishu during the invited guest ritual and o-kyaku. In this article, the author will discuss the presentation of tea by teishu in a sadoo ritual; how a teishu presents tea, what matters and what to watch for and do so that one can perform sadoo rituals, actions, movements and attitudes of a teishu during the sadoo ritual. These things are believed to be a reperesentation of the character of the Japanese known for its discipline, hardworking, thorough, diligent, well organized, manners, and ethics